1997
DOI: 10.1159/000170332
|View full text |Cite
|
Sign up to set email alerts
|

Viral Hepatitis in Continuous Ambulatory Peritoneal Dialysis Patients in an Endemic Area for Hepatitis B and C Infection: The Taiwan Experience

Abstract: The prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), and their associations in 64 continuous ambulatory peritoneal dialysis (CAPD) patients (30 males and 34 females) were evaluated. A comparison was also made with 526 normal controls (266 males and 260 females). Forty-seven (75%) CAPD patients were anti-HBc positive, with no significant difference to the control group (81.9%). This probably reflects acquisition of HBV infection by CAPD patients before initiation of chronic dialysis therapy in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Compared with the traditional organic liquid-liquid extraction, this CPE methodology requires a very small amount of relatively non-flammable and non-volatile surfactants. Also, compared with classical organic solvents, it offers the advantages of safety, low cost, high concentration efficiency, easy disposal of surfactants, low toxicity, less environmental pollution and simple procedure [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional organic liquid-liquid extraction, this CPE methodology requires a very small amount of relatively non-flammable and non-volatile surfactants. Also, compared with classical organic solvents, it offers the advantages of safety, low cost, high concentration efficiency, easy disposal of surfactants, low toxicity, less environmental pollution and simple procedure [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that hepatitis C virus (HCV) infection is not uncommon in Asian uremic patients receiving hemodialysis [15][16][17][18] . Studies have shown that HCV infection is an independent risk factor for death in chronic dialysis patients [19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Fisher and Wright [8] noticed an increased prevalence of pruritus in patients of hepatitis C virus (HCV) infection. Viral hepatitis is highly prevalent in dialysis patients [9][10][11][12][13]. Taiwan is one of the endemic areas with a high prevalence rate of viral hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Taiwan is one of the endemic areas with a high prevalence rate of viral hepatitis. In our previous work [11][12][13], we have demonstrated a high prevalence rate of hepatitis B virus (HBV) and HCV infection in our dialysis patients.…”
Section: Introductionmentioning
confidence: 99%